2012
DOI: 10.1002/anie.201205537
|View full text |Cite
|
Sign up to set email alerts
|

Facts are the Enemy of Truth—Reflections on Serendipitous Discovery and Unforeseen Developments in Asymmetric Catalysis

Abstract: As Louis Pasteur said, "Chance favors only a prepared mind." Serendipitous events reorienting the pathway of science often occur through the actions of dedicated individuals with unique cultural and educational backgrounds, an original sense of values, and firm principles. Science is the fountainhead of human knowledge and possesses an indispensable cultural value. Science-based technologies and the innovations derived from them are the foundation of the civilized society in which we live today. All scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…[24] This change may be ascribed to the occurrence of aweak interaction between the hydride and the guanidine proton, an interaction which is known to provoke as imilar effect in related organometallic systems. [25] Indeed, we found that when ap ure sample of [Rh(PPh 3 ) 3 H] is treated with 4equivalents of [H-tBuTMG]-[PF 6 ], as imilar broadening of the Rh À Hr esonance is observed. Furthermore,t he corresponding T 1 relaxation time of Rh I ÀHm easured at 300 Kd ecreases from 0.89 to 0.80 seconds (see Section S9), and is fully compatible with the occurrence of such weak H···H interaction.…”
Section: Methodsmentioning
confidence: 91%
“…[24] This change may be ascribed to the occurrence of aweak interaction between the hydride and the guanidine proton, an interaction which is known to provoke as imilar effect in related organometallic systems. [25] Indeed, we found that when ap ure sample of [Rh(PPh 3 ) 3 H] is treated with 4equivalents of [H-tBuTMG]-[PF 6 ], as imilar broadening of the Rh À Hr esonance is observed. Furthermore,t he corresponding T 1 relaxation time of Rh I ÀHm easured at 300 Kd ecreases from 0.89 to 0.80 seconds (see Section S9), and is fully compatible with the occurrence of such weak H···H interaction.…”
Section: Methodsmentioning
confidence: 91%
“…[1,6,7] This key parameter cannot always be measured experimentally, especially for high barriers, but it can be computed. To the best of our knowledge, despite the huge literature referring to BINAP applications based on Noyoris findings, [8,9] the enantiomerization barrier of BINAP 1 has not yet been explicitly reported. Nevertheless, such barriers have been calculated for less sterically congested related scaffolds, such as 1,1'-binaphthyl 3, [10,11] BINOL 2, [10,12,13] H-MOP 4, [14,15] and H-MIOP 5.…”
mentioning
confidence: 83%
“…One could argue that, for its simplicity, this is the most beautiful of all entries by Noyori, as this single structure depicts a powerful molecular catalyst that embraces a whole field of asymmetric synthesis: “The utility of Ru II is enormous, and provided a breakthrough in asymmetric hydrogenation chemistry. Since 1986, we have invented a range of BINAP/Ru catalysts, which allow for production of a wide range of enantiomeric organic compounds.” In all these cases, the asymmetry is induced by the C 2 ‐symmetric bisphosphine ligand BINAP, a molecular structure that Noyori had been drawn to from early on: “I decided to explore the general use of an atropisomeric C 2 ‐chiral binaphthyl scaffold for asymmetric synthesis and catalysis, because this artificial molecular architecture is quite simple and distinctly beautiful … The architectural characteristics of BINAP fit well with the sensibility of Japanese scientists (and perhaps scientists of some other ethnicities). The molecular beauty satisfies our sense of grace.…”
mentioning
confidence: 99%